Analiz obrašcenij za medicinskoj pomošc'ju olimpijskich atletov iz Rossii vo vremja XXIII Olimpijskich zimnich igr v Pchencchane v 2018 g. - Mirošnikova, Ju. V.; Puškina, T. A.; Žolinskij, A. V.; Velicko, M. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
Medical provision of athletes during Olympic Games is always challenging. Medical encounters to the Polyclinic of the Olympic village and to the National medical centers are somewhat different in pathology. The information about type and numbers of encounters to national centers is lacking. This article presents information on the quantity of encounters to the national medical staff working with OAR during Pyeongchang 2018 Olympic Games, as well as on the type of pathology present. The information would be useful for planning medical help during future winter sport events.